Optical and ac conductivity investigations on Sn doped Ag2S thin films under the structural transition framework. (February 2015) - Boughalmi, R.; Boukhachem, A.; Amlouk, M.
Abstract: This work deals with further optical and electrical investigations on Sn content in Ag2 S sprayed thin films and the beneficial effect of using this type of doping in addition to the results recently reported by R. Boughalmi, A. Boukhachem, I. Gaeid, K. Boubaker, M. Bouhafs, M. Amlouk, Mater. Sci. Semicond. Process. 16 (2013) 1584. The refractive index and extinction coefficient values in terms of Sn content were deduced from transmittance and reflectance data. Moreover, study of dielectric constants has been conducted; the dispersion parameters and high- frequency dielectric constant are determined. Finally, the electrical conductivity and conduction mechanism of these films are studied using an impedance spectroscopy technique in the frequency range 5 Hz–13 MHz at various temperatures (100–230 °C). Besides, the temperature dependence of ac conductivity measurements has been analyzed under the structural transition framework from β- to α-Ag2 S phases.